Social Innovation and International Relations: A Case Study on The Acceleration of Battery Electic Vehicle in Indonesia - Verdinand Robertua; Riskey Oktavian; Riantina Fitra Aldya Aldya (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
This article examines the acceleration of Battery Electric Vehicle (BEV) adoption in Indonesia through a dual-theoretical lens: Sandra M. Bates’ six-step social innovation framework and Jänicke and Jacob’s diffusion theory of environmental innovation. While Presidential Regulation No. 55 of 2019 formalizes Indonesia’s commitment to electric mobility, its underlying motivations, coherence, and systemic impact remain contested. Employing a qualitative case study methodology, the research draws on semi-structured interviews with stakeholders from civil society, policy networks, and EV user groups, as well as policy document analysis. The findings reveal that although the policy sequence aligns with Bates’ innovation stages—problem identification, prioritization, solution exploration, implementation, business model development, and diffusion—it does so within a fragmented governance context marked by coal-powered electricity, elite-focused infrastructure, and weak coordination across sectors. From the perspective of Jänicke and Jacob’s diffusion model, Indonesia’s trajectory reflects a technological initiative pathway, where global technological developments precede and shape reactive domestic policy. Rather than an internally driven transformation, BEV policy in Indonesia appears influenced by external climate obligations and domestic electricity surplus management, highlighting the role of structural dependency in shaping sustainability transitions. This study contributes to debates in International Relations and climate governance by showing how countries in the Global South navigate externally generated innovations within domestic constraints. It also proposes the need to adapt prevailing innovation frameworks to better capture asymmetric power relations and the contested nature of environmental transitions in developing contexts.Artikel ini mengkaji percepatan adopsi Kendaraan Listrik Berbasis Baterai di Indonesia melalui dua pendekatan teoretis: kerangka enam langkah inovasi sosial Sandra M. Bates dan teori difusi inovasi lingkungan Jänicke Jacob. Meskipun Peraturan Presiden Nomor 55 Tahun 2019 memformalkan komitmen Indonesia terhadap mobilitas listrik, motivasi mendasar, koherensi, dan dampak sistemiknya masih diperdebatkan. Dengan menggunakan metodologi studi kasus kualitatif, penelitian ini bersandar pada wawancara semi-terstruktur dengan pemangku kepentingan dari masyarakat sipil, jaringan kebijakan, dan kelompok pengguna EV, serta analisis dokumen kebijakan. Hasil penelitian menunjukkan bahwa, meski urutan kebijakan selaras dengan tahapan inovasi Bates- (1) identifikasi masalah, (2) prioritisasi, (3) eksplorasi solusi, (4) implementasi, (5) pengembangan model bisnis, dan (6) difusi—proses tersebut berjalan dalam konteks tata kelola terfragmentasi, yang ditandai oleh penggunaan listrik berbasis batubara, infrastruktur yang terpusat pada elit, dan koordinasi antarsektor yang lemah. Dari perspektif model difusi Jänicke Jacob, trajektori Indonesia mencerminkan jalur inisiatif teknologi, di mana perkembangan teknologi global mendahului dan membentuk kebijakan domestik yang bersifat reaktif. Alih‑alih merupakan transformasi yang digerakkan dari dalam, kebijakan BEV di Indonesia tampak dipengaruhi oleh kewajiban iklim eksternal dan upaya pengelolaan surplus listrik domestik, menggarisbawahi peran ketergantungan struktural dalam menuntun transisi keberlanjutan. Studi ini berkontribusi pada wacana Hubungan Internasional dan tata kelola iklim dengan menunjukkan bagaimana negara‑negara Global South menavigasi inovasi eksternal dalam kerangka domestik yang terbatas. Selain itu, penelitian ini mengusulkan perlunya adaptasi kerangka inovasi yang ada agar lebih mampu menangkap relasi kekuasaan asimetris dan sifat kontestasi transisi lingkungan di negara berkembang.